Successful Pregnancy Outcome in a Patient Treated with Pembrolizumab and Exposed to Fluoro-Deoxyglucose (18F-FDG) PET/CT: Case Report and Review of Literature - Anna Lucia Mastricci; Felice Sorrentino; Elisa Giansiracusa; Erika Zanzarelli; Graziana Silvana De Lucia; Vincenza Fernanda Fesce; Luigi Nappi; Lorenzo Vasciaveo (Biomedicines)
Background: Hodgkin lymphoma (HL) is a common malignancy among women of reproductive age. Some pregnancies occur during oncological treatments or diagnostic follow-ups, often involving contraindicated procedures. HL is fluorodeoxyglucose-avid; therefore, its staging is generally performed with 18F-FDG PET/CT, a diagnostic method contraindicated during pregnancy. Immune checkpoint inhibitors (ICIs), such as pembrolizumab, are innovative therapies for relapsed HL (rHL) with significant efficacy. However, ICIs can impair immune tolerance, potentially increasing immune-related adverse events. The PD-1/PD-L1 pathway, targeted by pembrolizumab, plays a critical role in maternal–fetal immune adaptation, raising concerns about its safety during pregnancy. Case Report: We report the case of a 36-year-old woman diagnosed with rHL who unknowingly became pregnant during treatment with pembrolizumab and 18F-FDG PET/CT scans. The pregnancy was diagnosed at 24 weeks, after five cycles of pembrolizumab during the first two trimesters and an 18F-FDG PET/CT scan in the first trimester. Following multidisciplinary counseling, the pregnancy was closely monitored, culminating in the delivery of a healthy male infant at 37.5 weeks. Conclusions: This case highlights a favorable maternal–fetal outcome despite exposure to pembrolizumab and 18F-FDG PET/CT during pregnancy. Given the limited data on such exposures, case reports like this are essential for improving counseling and management strategies. Further research and registries are crucial to provide robust evidence for clinical decision-making in these complex scenarios.